Development of a Full-Length Infectious cDNA Clone of the Grapevine Berry Inner Necrosis Virus - Xudong Fan; Zunping Zhang; Fang Ren; Guojun Hu; Chen Li; Baodong Zhang; Yafeng Dong (Plants, 2020)
Grapevine berry inner necrosis virus (GINV) belongs to the genus Trichovirus in the family Betaflexiviridae. The GINV isolate LN_BETA_RS was obtained from a “Beta” grapevine (Vitis riparia × Vitis labrusca) exhibiting chlorotic mottling and ring spot in Xingcheng, Liaoning Province, China. To verify the correlation between GINV and grapevine chlorotic mottling and ring spot disease, we constructed an infectious cDNA clone of GINV isolate LN_BETA_RS using the seamless assembly approach. Applied treatments of agroinfiltration infectious cDNA confirmed systemic GINV infection of the Nicotianaoccidentalis 37B by reverse transcription polymerase chain reaction (RT-PCR) and transmission electron microscopy, exhibiting chlorotic mottling symptoms on leaves. Infectious cDNA was also transmitted to new healthy N. occidentalis plants through rub-inoculation. Moreover, the cDNA clone was agroinfiltrated into “Beta” and “Thompson Seedless” grapevine plantlets, and the inoculated grapevines exhibited leaf chlorotic mottling and ringspot during the two years of observation. GINV-inoculated “Beta” grapevines had serious leaf chlorotic mottling and ringspot symptoms on the whole plant, while relatively few symptoms were observed on the leaves of agroinoculated “Thompson Seedless” grapevines in early spring and only weak ring spot gradually appeared later in the top young leaves. Our experiments fulfilled Koch’s postulates and revealed the causative role of GINV in grapevine chlorotic mottling and ring spot disease.